Graphics Drawing Workbook to accompany Technical Gaphics Communication and Fundamentals of Graphics Communication - R. Bertoline Gary (Mc Graw Hill, 2009)
There are workbook problems for every major topic normally taught in a engineering or technical drawing course. Most of problems can be drawn with instruments or ketched. A special emphasis had been put on freehand sketching in this workbook. It is expected that the instructor will supplement these problems with others from the text to fully reinforce technical drawing topics.